Memahami Ketertarikan Warga Negara Asing Terhadap Tradisi Percikan Tirta Suci Pada Patung Ganesha di Sahasra Adhi Pura, Sonosewu, Sukoharjo Sebagai Media Komunikasi Antar Budaya - Raditya, Ivo Dimas Ageng (Jurnal The Messenger, 2014)
This research aims to determine the factors of the main attraction foreign citizen to knows the sprinkling holy water on ganesha statue tradition at Sahasra Adhi Pura , Sonosewu , Sukoharjo .The theory used in this research adopted from Littlejohn ( 2009) , external stimuli generate an internal meanings that will generate a response to the outside. Signification itself internally divided into two parts: the internal response and internal stimuli. The question in this research is the dominant factor affecting an individual's interest to get to know other cultures. The question in this research what factor has dominant affecting   individual 's interest to know other cultures .The method used is non - participatory observation and in-depth interviews using qualitative descriptive analysis . This research was conducted in Sukoharjo . With interviews by a competent speaker is a professor of philosophy and culture of Java , while sampling using purposive sampling technique .It was concluded that the dominant factors affecting the interests of foreign citizen which are   condition of community attitudes towards immigrants openness and acceptance of differences, also the effectiveness of   word of mouth .